Analysis of Labor Absorption in East Kalimantan Province 2017-2021 - Tiara Oktafia Parastika; Eni Setyowati (Universitas Muhammadiyah Makassar, 2023)
Opening up job opportunities for the larger community is one method to foster fair prosperity, keeping in mind that society is one of the key determinants of an area's economy. Therefore, the purpose of this study is to ascertain the impact of the East Kalimantan Province's District Minimum Wage (UMK), Gross Regional Domestic Product (GRDP), and Human Development Index (IPM). Penelitian was conducted between the years of 2017 and 2021 in 10 cities and towns in the province of Kalimantan Timur using a data panel analysis tool called Eviews 9.0. According to the results of the analysis, it can be concluded that there is a positive relationship between the variables UMK and PDRB and the hiring of temporary workers in Kalimantan. Similar to this, the IPM variable shows a negative trend regarding the hiring of laborers in Kalimantan.